Depression among people living with HIV at a district hospital in KwaZulu-Natal, South Africa - Zothile L. Vezi; Selvandran Rangiah; Kantharuben Naidoo (South African Family Practice)
Background: Depression is a debilitating condition worldwide and a major contributor to the overall global burden of disease. The prevalence of depression is estimated to be higher in people living with HIV and AIDS (PLWHA) compared to the general population, with disease related complications increasing when mental health problems remain untreated. The aim of the study was to determine the prevalence of depression among PLWHA who attend a district hospital ART clinic in KwaZulu-Natal (KZN), South Africa (SA).